2015
DOI: 10.1152/physiol.00008.2015
|View full text |Cite
|
Sign up to set email alerts
|

The Physiology of Proinsulin C-Peptide: Unanswered Questions and a Proposed Model

Abstract: C-peptide is produced, processed, and secreted with insulin, and appears to exert separate but intimately related effects. In this review, we address the existence of the C-peptide receptor, the interaction between C-peptide and insulin, and the potential physiological significance of proinsulin C-peptide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 53 publications
(75 reference statements)
0
17
0
Order By: Relevance
“…C-peptide indicates insulin production since it is a by-product of the conversion of proinsulin to functional insulin. 23 Along with endocrine function, expression of transcription factor PDX1 could be seen. This transcription factor is central in β-cell function and survival.…”
Section: Discussionmentioning
confidence: 99%
“…C-peptide indicates insulin production since it is a by-product of the conversion of proinsulin to functional insulin. 23 Along with endocrine function, expression of transcription factor PDX1 could be seen. This transcription factor is central in β-cell function and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Over the course of the last two decades, proinsulin C‐peptide has gained recognition as a potential therapeutic target for the treatment of diabetes‐associated microvascular dysfunction . Although originally thought to be merely a byproduct of insulin prohormone processing, C‐peptide is now known to possess biological activities, particularly in the microvessels, and has been shown to exert anti‐inflammatory, anti‐oxidant and metabolic actions . Additionally, C‐peptide may act synergistically with insulin to maintain the vascular endothelium, although the mechanisms underlying this potential interaction have not been fully elucidated .…”
Section: C‐peptide and The Deductive Ligand–receptor Matching Strategymentioning
confidence: 99%
“…C‐peptide receptor ‘null’ cells) could complicate the isolation of the C‐peptide receptor(s). Likewise, because the actions of C‐peptide appear to be intimately linked with those of insulin , C‐peptide may exhibit cooperative binding with insulin, and thus, the efficient binding and purification of a C‐peptide receptor would require the presence of insulin. Therefore, isolation of the C‐peptide receptor based on its biochemical and binding properties may not be feasible.…”
Section: C‐peptide and The Deductive Ligand–receptor Matching Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…C-peptide levels in the peripheral blood are widely accepted as the most appropriate evaluation of insulin secretion, and are not eliminated in the first-pass metabolism through the liver [ 4 , 5 ]. Previously considered to be an inactive by-product of insulin synthesis, C-peptide is a hormonally active peptide [ 5 , 6 ]. In type 1 diabetes, an Italian study with a large clinical cohort demonstrated a significant association between C-peptide and microvascular complications, including neuropathy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%